A Survey on Security Issues in Web Services - Akunuri, Satyam; Perugu, Subbarao; Rajendra Prasad, B (International Journal of Computer Sciences and Engineering, 2025)
Web Service is a collection of software components which provide the services over the web. Web services are playing a key role in a wide range of modern business applications. The nature of loosely coupled connections and open accessibility may cause several security issues. Recently, a number of new standards and protocols have been introduced. When deploying a web service, security is one of the major issue that need to be addressed. In this paper, we discuss the possible threats to web services and recommend preventive measures.